2010
DOI: 10.1097/hjh.0b013e32833a38f2
|View full text |Cite
|
Sign up to set email alerts
|

Social disparities in prevalence, treatment and control of hypertension in Iran: Second National Surveillance of Risk Factors of Noncommunicable Diseases, 2006

Abstract: In Iran, there is comparatively higher prevalence of hypertension among people of Kurdish ethnicity, people of low education and in high-Human Development Index provinces; a lower treatment rate among men, younger people, people of low education and low income; and a lower control rate among men and people of low education. These disparities should be addressed by researchers and health policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
3
33
2
Order By: Relevance
“…Studies examining wealth-related inequalities are much fewer in number, however the pro-rich inequalities observed for detection and control observed in our study were consistent with previous findings in China, India and South Africa [5]; as were other study findings regarding hypertension treatment rates in Brazil [30], China [31], Iran [29] and Tanzania [32]. Finally, a recent Canadian study of adults using national data found no evidence for income-related inequality with respect to hypertension detection or control [33], while we observed a small, albeit significant, pro-poor distribution for detection but not control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies examining wealth-related inequalities are much fewer in number, however the pro-rich inequalities observed for detection and control observed in our study were consistent with previous findings in China, India and South Africa [5]; as were other study findings regarding hypertension treatment rates in Brazil [30], China [31], Iran [29] and Tanzania [32]. Finally, a recent Canadian study of adults using national data found no evidence for income-related inequality with respect to hypertension detection or control [33], while we observed a small, albeit significant, pro-poor distribution for detection but not control.…”
Section: Discussionsupporting
confidence: 92%
“…While the rates of awareness, treatment and control in Sweden were substantially lower than the other high-income PURE countries, they were similar to those in an earlier study that used data from the WHO MONICA (Multinational MONItoring of trends and determinants in CArdiovascular disease) Project [28]. In Iran, data from the National Surveillance of Risk Factors for NCDs also showed a similarly large attrition in the pathway of hypertensive individuals from detection through treatment to control (33% treated and 12% controlled, respectively, compared with 51 to 18% in our study) [29]. A recent paper combined data from SAGE (WHO Study on global AGEing and adult health) and COURAGE (Collaborative Research on Ageing in Europe), with data on hypertension prevalence by household wealth [5].…”
Section: Discussionsupporting
confidence: 87%
“…2 Most importantly, direct age standardisation to the 35-69 years WHO World Standard Population 17 (26.6%; 25.5% to 27.6%), allows comparison with Egypt (33.8%), 21 Iran (34.1%) 22 or Turkey (34.2%). 23 The low prevalence of hypertension, besides any methodological consideration, might thus be related to the possibility that Yemen is behind in the epidemiological transition currently ongoing in other countries of the Middle East Crescent area.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is a country with diverse ethnicities, languages, and priorities (38). Therefore, these differences and priorities, as well as people's needs and beliefs, should be taken into consideration in the design of training programs in HHs.…”
Section: 1mentioning
confidence: 99%